IPO Initial Underpricing Anomaly: the Election Gimmick Hypothesis - Zaremba, Adam; Żmudziński, Radosław (Copernican Journal of Finance & Accounting, 2014)
The relationship between political motivations and underpricing of public offerings of privatized companies is to a great extend unexplored field in the global academic literature. In this paper we offer a new explanation for the IPO underpricing anomaly. We formulate the election gimmick hypothesis, which states that in order to please the voters the treasury may be motivated to leave some money on the table during the IPOs of state-owned enterprises. We test the practical implications of the hypothesis. First we review the previous literature, next we perform empirical research based on a filtered sample of 250 IPOs on the Polish market in years 2005–2013. We examine the abnormal returns in the sample and employing some regression – and simulation- -based methods we examine the sources and variation in underpricing. Our findings suggest that the IPOs of state-owned enterprises are more underpriced than remaining ones and that there is more money left on the table in the months preceding elections.